ANALISIS PERAN SUKUK AL-INTIFA’A SEBAGAI INSTRUMEN DALAM MENGENTASKAN KEMISKINAN DI INDONESIA - Wiratama, Dadang; Putra, Bintang Ramadhan (I-Economics, 2020)
Abstract Today the capital market is one of the instruments that plays an important role in the economy of developed and developing countries. For developing countries like Indonesia, the capital market is an economic potential that is able to offer solutions to capital problems that are often faced in the context of national development. Especially when efforts to obtain additional capital through loans are felt to be increasingly unprofitable. Likewise with the Islamic capital market, although it is still new when compared to other Islamic financial instruments, the development of the Islamic capital market in Indonesia is considered quite good. One of the sharia financial instruments that is an important financing for the state budget is sukuk. At home, sukuk are growing quite rapidly although the proportion is still relatively small compared to conventional markets. This will be able to support the development of the Islamic capital market in Indonesia, especially if it is able to capture the opportunities that exist. One such opportunity is waqf assets which are widely available in various regions in Indonesia and many are still not being worked productively. Dual integration between sukuk and waqf in Al Intifa‘a Sukuk is expected to be able to create a financial instrument that can boost economic development and alternatives for poverty alleviation efforts in Indonesia. Keyword: Sukuk, Waqf, Poverty, Islamic Capital Market Abstrak Dewasa ini pasar modal menjadi salah satu instrumen yang memainkan peranan penting dalam perekonomian negara maju maupun berkembang. Bagi negara berkembang seperti Indonesia, pasar modal merupakan potensi perekonomian yang mampu menawarkan solusi bagi permasalahan permodalan yang sering dihadapi dalam rangka pembangunan nasional. Terlebih ketika upaya perolehan tambahan modal melalui pinjaman dirasa semakin tidak menguntungkan. Demikian halnya dengan pasar modal syariah, walaupun masih baru jika dibandingkan dengan instrumen keuangan syariah yang lain, tapi perkembangan pasar modal syariah di Indonesia dinilai cukup baik, Salah satu instrumen keuangan syariah yang menjadi pembiayaan penting bagi anggaran negara adalah sukuk. Di dalam negeri sendiri, sukuk tumbuh cukup pesat walaupun proporsinya masih relatih kecil dibandingkan dengan pasar konvensional. Hal ini akan mampu menunjang perkembangan pasar modal syariah di Indonesia, apalagi jika mampu menangkap peluang yang ada. Salah satu peluang tersebut adalah aset wakaf yang banyak terdapat di berbagai wilayah di Indonesia dan masih banyak yang belum tergarap secara produktif. Dual integrasi antara sukuk dan wakaf dalam Sukuk Al Intifa‘a diaharapkan mampu menciptakan sebuah instrumen keuangan yang bisa mendongkrak pembangunan ekonomi dan seabgai alternatif dalam upaya pengentasan kemiskinan di Indonesia. Kata kunci : Sukuk, Waqf, Kemiskinan, Pasar Modal Syariah